Pengaruh Pengembangan Sumber Daya Manusia dengan Transformasi Digital terhadap Keunggulan Kompetitif Berkelanjutan dengan Peran Mediasi Perilaku Inovatif - Arif, Donny; Safitri, Mita Uji; Martah, Varid (Universitas Nahdlatul Ulama Surabaya, 2023)
This research aims to find out whether human resource development with digitaltransformation and innovative behavior has an influence on the sustainable competitive advantageof SMEs in Surabaya. This research uses a questionnaire to collect data with a population of SMEsin Surabaya of 59,969 and samples were taken using the Slovin formula with a result of 99.83 andwill be rounded to 100. The method used in this research is descriptive quantitative analysis withcomparative causality and path analysis. The results of this research show 1) human resource development has a positive and significant effect on innovative behavior, 2) human resourcedevelopment has a positive and significant effect on sustainable competitive advantage, 3)innovative behavior has a positive and significant effect on sustainable competitive advantage, 4)digital transformation positive and significant effect on innovative behavior, 5) digitaltransformation has a positive and significant effect on sustainable competitive advantage